Organizational and clinical aspects of acute coronary syndrome combined with a new coronavirus infection (SARS-COV-2) - I. I. Serebrennikov; Ph. Yu. Kopylov; R. N. Komarov; M. B. Mukanova; A. M. Ismailbaev; F. S. Gafurov (Евразийский Кардиологический Журнал, 2023)
Objective. Assessment of organizational and clinical aspects of acute coronary syndrome combined with a new coronavirus infection (SARS- CoV-2).Materials and methods. This is a retrospective study where 60 patients were divided into the following groups: group 1 patients with acute coronary syndrome (ACS) and a new coronavirus infection hospitalized in the «red» zone after infection was detected at the prehospital stage (n=29); group 2 - uninfected coronavirus infection patients with ACS (n=31). The primary points were mortality in the hospital and the average time (up to 2 months) after ACS, the incidence of acute heart failure, the incidence of ACS with ST segment elevation, the frequency of acute coronary artery occlusions.Results. The analysis of hospital mortality revealed its higher level in the ACS group and COVID-19 (group 1) (p=0.009). Mortality within 2 months was also higher in group 1 (p=0.017). The groups did not differ in the number of patients with ACS and ST segment elevation and acute coronary artery occlusions. Analysis of the incidence of OSN at admission revealed a statistically significant difference (p=0.05) in group 2 (n=12, 38.7%) compared with group 1 (n=5, 17.2%).Conclusions. Patients with ACS and COVID-19 are characterized by a higher initial severity, a tendency to develop ACS with ST segment elevation, high rates of hospital and 60-day mortality. Separating the flows of infected and uninfected patients makes it possible to improve the epidemiological situation in non-infectious hospitals, however, it leads to a delay in hospitalization of patients with ACS and COVID-19, which potentially increases the risk of fatal complications in this cohort.